2015
DOI: 10.1007/s00394-015-0961-7
|View full text |Cite
|
Sign up to set email alerts
|

Baccaurea angulata fruit inhibits lipid peroxidation and induces the increase in antioxidant enzyme activities

Abstract: Our results show that B. angulata fruit is beneficial in positively influencing and managing oxidative damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 57 publications
(56 reference statements)
0
14
0
Order By: Relevance
“…Besides the total energy intake, the diet composition also has a significant effect on the metabolic and endocrine functions as well as the overall energy balance (Dongiovanni et al, 2016). Therefore, the consumption of diets which are rich in fruits and vegetables is highly recommended for the prevention of oxidative damage and chronic disease (Mikail et al, 2016), and NAFLD is not an exception. Plants and plant-based natural products (such as fruit, vegetables, minimally-refined cereal, medicinal and aromatic plants) are sustainable antioxidant sources containing novel biologically active compounds such as phenolic compounds and vitamins with known beneficial effects (Ahmed and Mikail, 2017, Ahmed et al, 2015, Ahmed et al, 2017a, Ahmed et al, 2017b, Ibrahim et al, 2017a, Ibrahim et al, 2017b).…”
Section: Management Of Nafldmentioning
confidence: 99%
“…Besides the total energy intake, the diet composition also has a significant effect on the metabolic and endocrine functions as well as the overall energy balance (Dongiovanni et al, 2016). Therefore, the consumption of diets which are rich in fruits and vegetables is highly recommended for the prevention of oxidative damage and chronic disease (Mikail et al, 2016), and NAFLD is not an exception. Plants and plant-based natural products (such as fruit, vegetables, minimally-refined cereal, medicinal and aromatic plants) are sustainable antioxidant sources containing novel biologically active compounds such as phenolic compounds and vitamins with known beneficial effects (Ahmed and Mikail, 2017, Ahmed et al, 2015, Ahmed et al, 2017a, Ahmed et al, 2017b, Ibrahim et al, 2017a, Ibrahim et al, 2017b).…”
Section: Management Of Nafldmentioning
confidence: 99%
“…These versatile health benefits exerted by B. angulata WF may be partly due to the fact that phenolic compounds which act as excellent antioxidants indirectly contribute to anti-inflammatory action. Baccaurea angulata WF that possessed the potential to minimize the generation of free radicals and displayed high antioxidant properties and protective effect against lipid peroxidation, a promoter of the atherosclerotic event [ 16 ], also interferes with the inflammatory stage of atherosclerosis. Our results are in accordance with a previous experimental study which showed that polyphenol-rich Euterpe oleracea Martius (Arecaceae), commonly known as açaí, possessed both antioxidant and anti-inflammatory properties through the reduction of lipid peroxidation, boosting of antioxidant enzymes, and inhibition of proinflammatory cytokine production [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Island of Malaysia and several other regions of Indonesia [14]. The high antioxidant levels of B. angulata had opened a new possibility of developing it as herbal preparations that has a high potential for producing nutraceutical benefits our wellbeing.…”
Section: Fruitmentioning
confidence: 99%